Botryomycosis: A surprising revelation in the lacrimal sac. (4th May 2018) - Dsouza, Susan; Kamath, Gurudutt M.; Kamath, Ajay R.; Sahoo, Kausalyakumari; Sharma, Harshita
ABSTRACT: A middle aged woman presented to us with a localised well defined swelling of 3 months duration. It was located just below the lower eyelid punctum and was constantly discharging whitish granules. We suspected it to be arising from the lacrimal apparatus and posted the patient for Dacryocystectomy. On the operating table we found a swelling in the region of the lacrimal sac which was later excised. Histopathology revealed Botryomycosis and Chronic Dacryocystitis. Botryomycosis is a rare condition and requires a high index of suspicion to diagnose it. It is confirmed by histopathology and culture. Surgical debridement is the treatment of choice in such cases with an assessment of the immune status. Long term antibiotic treatment is required in all conditions as recurrence is common.